Association between body composition indices and vascular health: a systematic review and meta-analysis - Mohammad Nikoohemmat; Amirhossein Ramezani Ahmadi; Ali Valizadeh; Seyed Mohammadmisagh Moteshakereh; Reza Yari-Boroujeni; Zahra Seifi; Majid Valizadeh; Behnaz Abiri (Eating and Weight Disorders)
Abstract Objective This systematic review explores the intricate relationship between body composition, with a specific focus on skeletal muscle mass, and vascular health indices, including measures of arterial stiffness—pulse wave velocity (PWV) and cardio-ankle vascular index (CAVI)—as well as arterial structure, specifically carotid artery intima–media thickness (cIMT). Methods An extensive literature search, encompassing PubMed, Scopus, EMBASE, Web of Science, and Google Scholar, was conducted until January 2024. Inclusion criteria involved original observational studies, with cross-sectional or longitudinal designs, reporting body composition parameters and vascular health measures. The Newcastle–Ottawa Scale (NOS) assessed study quality. Statistical analyses utilized Stata 17.0, employing random-effects meta-analysis, sensitivity analysis, and evaluation of publication bias. Results Fifteen observational studies (n = 21,215) met the inclusion criteria. Pooled analyses revealed a positive association between fat-free mass (FFM) and carotid intima–media thickness (IMT) (effect size [ES]: 1.79, 95% CI 1.68–1.91), highlighting a relationship with arterial structure. Similarly, body fat percentage (BFP) was positively associated with PWV (ES: 1.45, 95% CI 1.15–1.82), and FFM showed a positive association with CAVI (ES: 1.46, 95% CI 0.78–2.71), both measures of arterial stiffness. Subgroup analyses revealed a non-significant association between appendicular skeletal muscle (ASM) and IMT (ES: 1.01, 95% CI 0.76–1.35). Conclusion This meta-analysis highlights the complex relationship between body composition and vascular health. Subgroup analyses suggest the need for further research into specific body composition indices and their clinical implications. Level of evidence: III evidence obtained from well-designed cohort and cross-sectional studies.